Lexical combinatorics and meaning profiling of the French lexeme ’embryon’ - Cozma, Ana-Maria; Lehtonen, Kim (Neuphilologische Mitteilungen, 2024)
This article studies the lexical combinatorics of the French word embryon and how the meaning of this word is profiled from one phrase to another. The study is based on a bioethics corpus made up of institutional discourses on the one hand, and internet users’ comments on the other. A concordance tool was used to extract all the phrases in which the word embryon occurs, whatever their frequency. The phrases thus listed are presented first from the point of view of syntactic combinatorics, then from the point of view of lexical combinatorics, and constitute the data that we will analyse. Thus, although extracted from actual discourse, the phrases have undergone simplifications that place them more at a prediscursive level. To carry out the study of these syntagms, the analysis model chosen is Olga Galatanu’s Semantics of Argumentative Possibilities (SPA), to which we have added the notion of profiling (Cadiot and Visetti), understood as the result of a process of convocation-evocation, according to Victorri’s vision of gestalt compositionality. The actual analysis consists of identifying the argumentative associations activated by the phrases: the DAs, on the one hand, and the associations evoked by the lexical combinatorics, on the other.